Written discourse in diagnosis for acquired neurogenic communication disorders: current evidence and future directions - Kim, Hana; Obermeyer, Jessica; Wiley, Robert W. (Frontiers in Human Neuroscience, 2024)
Purpose: We aimed to perform the first review of research focusing on written discourse performance in people with acquired neurogenic communication disorders. In studies from 2000 onward, we specifically sought to determine: 1) the differences between patient populations and control groups, 2) the differences between different patient populations, 3) longitudinal differences between patient populations, and 4) modality differences between spoken and written discourse performance.Method: We completed a thorough search on MEDLINE, Embase, Cochrane, APAPsycinfo, Web of Science, and Scopus databases. We identified studies that focus on written discourse performance in people with aphasia, primary progressive aphasia, mild cognitive impairment, and Alzheimer's disease.Results: Nineteen studies were identified from the review of literature, some of which addressed more than one of our review questions. Fifteen studies included a comparison between clinical populations and controls. Six studies compared different characteristics of patient populations. Three studies reported changes over time in progressive disorders. Six studies targeted different modalities of discourse.Conclusions: Differences in linguistic features by patient populations are not yet clear due to the limited number of studies and different measures and tasks used across the studies.Nevertheless, there is substantial evidence of numerous linguistic features in acquired neurogenic communication disorders that depart from those of healthy controls. Compared to the controls, people with aphasia tend to produce fewer words, and syntactically simpler utterances compared to the controls. People with Alzheimer's disease produce less information content, and this feature increases over time, as reported in longitudinal studies.Our review imparts additional information that written and spoken discourse provide unique insights into the cognitive and linguistic deficits experienced by people with aphasia,